PEMBERDAYAAN UMKM PEMBUATAN TAHU GORENG DALAM MENINGKATKAN PEREKONOMIAN KELUARGA DI PASIR PUTIH KELURAHAN SUKAJADI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Wahidin, Wahidin; Wagisri, Wagisri; Sundari, Sri (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
This research aims to determine the Empowerment of MSMEs in Making Fried Tofu in Improving the Family Economy in Pasir Putih, Sukajadi Village, Talang Kelapa District, Banyuasin Regency. The focus of this research is the Empowerment of MSMEs in Making Fried Tofu in Improving the Family Economy in Pasir Putih, Sukajadi Village, Talang Kelapa District, Banyuasin Regency, which will be analyzed by adopting the theory of Community Empowerment according to Sumodiningrat (2000): Dimensions of increasing income; dimensions of capacity development; and dimensions of ability development. The results of the research are in the dimension of increasing income, the economic level of the white sand community can increase income and can send children to school until they graduate, then in the dimension of capacity development, the tofu making business is still very promising with large market potential and minimal competitiveness, then in the dimension of development ability, people innovate various tofu products such as pregnant tofu and gejrot tofu.